Antibacterial Activity of Several Types of Weed Extracts on The Growth of Escherichia coli - Dwi Nur Rikhma Sari; Septarini Dian Anitasari; Intan Choirul Uliyah (Pandawa Institute, 2023)
Escherichia coli is a type of Gram-negative bacteria that is commonly found in the human digestive tract. It has been reported as one of the bacteria that has been resistant to several antibiotics. This study aims to determine four (4) types of weed extracts that are considered but have not been used as antibacterial compounds against E. coli. This experimental study used a completely randomized design with several types of plant extracts, namely Acalypha indica L., Ageratum conyzoides, Phyllanthus niruri L., and Amaranthus spinosios at various concentrations (0, 50, and 100%). The results showed that the plant extract of A. indica L. had the ability as an antibacterial against the growth of E. coli at concentrations of 50% (1.41 ± 0.12) and 100% (1.53 ± 0.01) compared to other extracts. Meanwhile, the lowest average diameter of the inhibition zone for E. coli bacteria was found in the treatment of A. spinosios grass leaf extract 50% (1.17 ± 0.05).